Dogs demystified : an A-to-Z guide to all things canine - Bekoff, Marc (New World Library, 2023)
"An easy-to-read A-to-Z guide of 'all things dog.' The book largely focuses on dog behavior - what dogs do and why they do it - in order to help readers understand, appreciate, and peacefully coexist with dogs"--